The association between early introduction of tiny tastings of solid foods and duration of breastfeeding - Jenny Stern; Eva-Lotta Funkquist; Maria Grandahl (International Breastfeeding Journal, 2023)
Abstract Background Conflicting advice and non-evidence-based recommendations have a negative effect on breastfeeding. Since 2011, the National Food Agency in Sweden has informed parents that they can introduce tiny tastings (1 mL of solid food, i.e. other sources of nutrition than breastmilk/formula) to infants from four months of age. It is unknown how national recommendations, which differ from the Word Health Organisation’s recommendation, affect breastfeeding. We hypothesised that introduction of tiny tastings of solid foods would shorten the duration of continued breastfeeding. Methods This retrospective study utilises data from the longitudinal ‘Swedish Pregnancy Planning Study’, in which mothers were recruited at antenatal clinics on a national level. The participants completed three questionnaires up to one year after birth (n = 1,251). Linear regression models were used to analyse the association between the introduction of solid foods and the duration of breastfeeding. Results As hypothesised, introduction of tiny tastings shortened the duration of continued breastfeeding. Half of all infants (48%) were fed with tiny tastings already in the fourth month. The correlation analysis showed that the earlier the infants started with tiny tastings, the earlier they ate larger amounts of solid food. In a multivariate linear regression analysis, five factors were identified as having a negative effect on the duration of breastfeeding: low infant age upon introduction of tiny tastings, low maternal age, low level of maternal education, high maternal BMI and twin birth. Conclusions Early introduction of tiny tastings of solid foods shortened the duration of breastfeeding. It is difficult to influence most conditions that affect breastfeeding, for example, the mother’s educational level, BMI, age and if she has given birth to twins. In contrast, national guidelines can always be updated. Recommendations from the Swedish authorities should adhere to the WHO’s recommendation, which states exclusive breastfeeding for six months and continued breastfeeding for at least two years or longer.